J-2156, a small molecule somatostatin type 4 receptor agonist, alleviated hindpaw hypersensitivity in the streptozotocin-induced rat model of painful diabetic neuropathy but with a 2-fold decrease in potency at an advanced stage in the model, mimicking morphine - Kuo, A.; Imam, M. Z.; Li, R.; Lin, L.; Raboczyj, A.; Bohmer, A. E.; Nicholson, J. R.; Corradini, L.; Smith, M. T. (Frontiers in Pharmacology, 2024)
There is a large unmet need for novel pain-killers to improve relief of painful diabetic neuropathy (PDN). Herein, we assessed the efficacy of the somatostatin type 4 (SST4) receptor agonist, J-2156, for relief of PDN in rats. Diabetes was induced with streptozotocin (STZ; 70 mg/kg) and bilateral hindpaw hypersensitivity was fully developed by 8-weeks post-STZ. In the intervals, 8 to 12-weeks (morphine-sensitive phase; Phase 1) and 16 to 18-weeks (morphine-hyposensitive phase; Phase 2) post-STZ, rats received a single dose of intraperitoneal (i.p.) J-2156 (10, 20, 30 mg/kg), gabapentin (100 mg/kg i.p.), subcutaneous morphine (1 mg/kg) or vehicle. Hindpaw withdrawal thresholds (PWTs) were assessed using von Frey filaments pre-dose and at regular intervals over 3-h post-dose. In Phase 1, J-2156 at 30 mg/kg evoked significant anti-allodynia in the hindpaws with maximal effect at 1.5 h compared with 1 h for gabapentin and morphine. The durations of action for all three compounds were greater than 3 h. The corresponding mean (± SEM) extent and duration of antiallodynia (PWT AUC) for gabapentin did not differ significantly from that for J-2156 (30 mg/kg) or morphine. However, in Phase 2, the PWT AUC for morphine was reduced to 25% of that in Phase 1, mirroring our previous work. Similarly, the mean (± SEM) PWT AUC for J-2156 (30 mg/kg) in Phase 2 was ~45% of that for Phase 1 whereas for gabapentin the mean (± SEM) PWT AUCs did not differ significantly (P>0.05) between the two phases. Our findings further describe the preclinical pain relief profile of J-2156 and complement previous work in rat models of inflammatory pain, neuropathic pain and low back pain. SST4 receptor agonists hold promise as novel therapeutics for the relief of PDN, a type of peripheral neuropathic pain that is often intractable to relief with clinically used drug treatment options.